Kudus Cohort Study: a Two-Year Nutritional Observation of Newborn Cohort under Gemas (Gerakan Menjaga Periode Emas) Initiative. - Farid A Rahmadi; Ari Budi Himawan; Ahmad Syaifuddin; Arif Faiza; Andini Aridewi; Dony Wicaksana; Isna Noor Khilda; Devy Ayu Kurniati; Noor Hasyim Afro; Sudarmono; Doctors Closed Group; Anwar Santoso; Widjaja Lukito (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Maternal and child nutritional issues remain significant public health challenges in Indonesia. Longitudinal cohort data on growth and development from pregnancy through early childhood are scarce. This study describes the nutritional status of a cohort of children assessed at birth and at 6, 12, and 24 months. This operational study included 3,895 newborn infant, 874 children followed from birth to 2 years, and 110 children tracked over the same period. Anthropometric measurements of body weight and length were collected. Findings indicate that stunting should not be the sole focus when assessing nutritional status in children up to 2 years of age. Wasting also persists as a significant nutritional issue, with its prevalence increasing when the exclusive breastfeeding period was completed. Low birth weight (LBW) is recognized as a key determinant of infant growth and development through 12 months. Implementation of a single-package intervention in the Gemas Maternal and Child Health Program was effective in promoting catch-up growth among cohort children following the exclusive breastfeeding period.